Spacetime in the Poetry of Abd al-Rahman al-Dakhel in the Light of Bakhtin’s Theory - Al-Baradi, Fatima Bint Saleh (Arts for Linguistic & Literary Studies, 2024)
The research endeavors to engage in critical analysis of the poetry of Abd al-Rahman al-Dakhel, utilizing spacetime theory to explore ancient poetic texts. It seeks to provide a nuanced examination that adds a historical and geographical dimension to literary research, enriching scholarly discourse with varied perspectives. The study aims to stimulate further comprehensive investigations by offering insights into methodology and sample selection. Structured into an introduction, thematic sections, and findings, the research navigates between theoretical frameworks and practical application. It begins by elucidating the concept of spacetime according to Mikhail Bakhtin and its relation to previous theories on the interplay of time and space. Additionally, it delves into the biography of Abd al-Rahman al-Dakhel, contextualizing his significance within Arab and Islamic history, civilization, and literature. The study concludes that while Bakhtin's spacetime theory holds promise, its practical application in modern studies, particularly in narrative and poetry analysis, remains underdeveloped. Exploring poetic texts through this lens proves to be a critical endeavor, challenging the researcher's interpretive skills. Analyses of subsequent spacetime dimensions reveal insights into the social and psychological aspects embedded within the poetry. These dimensions intertwine, with the psychological aspect reflecting themes of disappointment, nostalgia, and separation, evoked through imagery such as the palm tree and memories characterized by emptiness and estrangement.